Detection of Salmonella human carriers in Colombian outbreak areas - Carvajal-Restrepo, Hernán; Sánchez-Jiménez, Miryan Margot; Diaz-Rodríguez, Sergio; Cardona-Castro, Nora (The Journal of Infection in Developing Countries, 2017)
Introduction: Salmonellosis, a zoonotic and foodborne disease, is a public health problem in developing countries. With the aim of identifying human carriers of Salmonella, a survey was performed in five regions of Colombia with reported salmonellosis outbreaks. Methodology: The general population and cholecystectomy surgical patients were included in this study. Stool samples from 667 volunteers and gallbladder bile samples from 199 surgical patients were examined. Detection of Salmonella from cultured stool and bile samples was determined by polymerase chain reaction (PCR). Multiplex PCR and biochemical and serological tests were performed to identify the serovars of the isolates. Results: Nine (1.35%) stool samples were positive for Salmonella: two S. Newport, two S. Anatum, one S. Sinstorf, and four Salmonella spp. A total of 11 gallbladder bile samples were positive: S. Enteritidis was isolated from 3 bile cultures (1.5%), and 8 samples (4%) were positive for Salmonella spp. Conclusions: Our results show the presence of Salmonella carriers in the inhabitants of regions with reported outbreaks and suggest that these carriers are potential sources of infection in endemic and epidemic cases. Carriers also suggest Salmonella zoonotic transmission, since broiler and beef cattle are hosts to the Salmonella serotypes isolated. It is important to establish the source of infection in regions where salmonellosis is endemic in order to control transmission.